Native language experience shapes pre‐attentive foreign tone processing and guides rapid memory trace build‐up: An ERP study. (16th March 2022) - Gosselke Berthelsen, Sabine; Horne, Merle; Shtyrov, Yury; Roll, Mikael
Abstract: Language experience, particularly from our native language (L1), shapes our perception of other languages around us. The present study examined how L1 experience moulds the initial processing of foreign (L2) tone during acquisition. In particular, we investigated whether learners were able to rapidly forge new neural memory traces for novel tonal words, which was tracked by recording learners' ERP responses during two word acquisition sessions. We manipulated the degree of L1–L2 familiarity by comparing learners with a nontonal L1 (German) and a tonal L1 (Swedish) and by using tones that were similar (fall) or dissimilar (high, low, rise) to those occurring in Swedish. Our results indicate that a rapid, pre‐attentive memory trace build‐up for tone manifests in an early ERP component at ~50 ms but only at particularly high levels of L1–L2 similarity. Specifically, early processing was facilitated for an L2 tone that had a familiar pitch shape (fall) and word‐level function (inflection). This underlines the importance of these L1 properties for the early processing of L2 tone. In comparison, a later anterior negativity related to the processing of the tones' grammatical content was unaffected by native language experience but was instead influenced by lexicality, pitch prominence, entrenchment, and successful learning. Behaviorally, learning effects emerged for all learners and tone types, regardless of L1–L2 familiarity or pitch prominence. Together, the findings suggest that while L1‐based facilitation effects occur, they mainly affect early processing stages and do not necessarily result in more successful L2 acquisition at behavioral level. Abstract : Our findings add important evidence that contributes to answering the open question of how similarity between native and target language influences target language processing and acquisition. We found facilitative effects of similarity only at pre‐attentive levels and only when the degree of similarity was high. Late processing and successful acquisition, on the other hand, were unaffected by the target words' similarity to native language properties.